Algal Diversity of Tahsil Parola, District Jalgaon, Maharashtra (International Journal of Scientific Research in Science and Technology, 2025)
During July 2013- April 2014 some algae were recorded from tehsil Parola. In the present paper, Nostocales with 14 members of oscillatoriaceae and 3 members of Nostocaceae were observed.
Keywords: diversity; algae; cynophyceae; Nostocales; Oscillatoriaceae; Nostoceae